The "right" way is not always popular: comparison of surgeons' perceptions during laparoscopic cholecystectomy for acute cholecystitis among experts from Japan, Korea and Taiwan. (22nd January 2017) - Hibi, Taizo; Iwashita, Yukio; Ohyama, Tetsuji; Honda, Goro; Yoshida, Masahiro; Takada, Tadahiro; Han, Ho‐Seong; Hwang, Tsann‐Long; Shinya, Satoshi; Suzuki, Kenji; Umezawa, Akiko; Yoon, Yoo‐Seok; et al.
Abstract: Background: Generally, surgeons' perceptions of surgical safety are based on experience and institutional policy. Our recent pilot survey demonstrated that the acceptable duration of surgery and criteria for open conversion during laparoscopic cholecystectomy (LC) vary among workplaces. Methods: A web‐based survey was distributed to 554 expert LC surgeons in Japan, Korea, and Taiwan. The questionnaire covered LC experience, safety measures and recognition of landmarks, decision‐making regarding conversion to open/partial cholecystectomy and the implications of this decision. Overall responses were compared among nations, and then stratified by LC experience level (lifetime cases 200–499, 500–999, and ≥1, 000). Results: The response rate was 92.6% (513/554); 67 surgeons with ≤199 LCs were excluded, and responses from 446 surgeons were analyzed. We observed significant differences among nations on almost all questions. Differences that remained after stratification by LC experience were on questions related to acceptable duration of surgery, adoption rates of intraoperative cholangiography, the "critical view of safety" technique, identification of Rouvière's sulcus, recognition of the SS‐Inner layer theory, and intraoperative judgment to abandon conventional LC. Conclusions: Even among experts, surgeons' perceptions during LC are workplace‐dependent. A novel grading system of surgical difficulty and standardized LC procedures are paramount to generate high‐level evidence. Abstract : In this multinational survey on variability in surgical strategy among laparoscopic cholecystectomy experts, Hibi and colleagues found significant differences in acceptable surgical duration, adoption of safety measures, recognition of anatomical landmarks, and intraoperative conversion to open/partial cholecystectomy. Surgeons' perceptions were workplace‐dependent, illustrating the need for a new grading system of surgical difficulty.